Մանկական գիրքը Ռուբեն Մանուկյանի ձևավորումներում - Սերգեյ Աբովյան (ՀՀ ԳԱԱ հրատ.)
В статье исследуется книжная графика Рубена Манукяна. Здесь беспрепятственно переплетаются оптимистическая красочная палитра с фантазией, одинаково привлекая внимание как знатоков, так и нетребовательных зрителей. Его стиль напоминает декоративную абстракцию, хотя и не является отражением чистого стиля. The article is a study of Ruben Manukyan’s book graphics. His ventures is confined within single components of the book, a forzats , an aperture, a cap and so on thus creating a unified line, which composes the book as a solid homogeneous composition.
Keywords: Biography; Decorative arts; Applied arts; Decoration and ornament; Illuminating of Manuscripts and Books